2013
DOI: 10.1095/biolreprod.112.103705
|View full text |Cite
|
Sign up to set email alerts
|

Change of Genes in Calcium Transport Channels Caused by Hypoxic Stress in the Placenta, Duodenum, and Kidney of Pregnant Rats1

Abstract: Preeclampsia is a pregnancy-specific disease characterized by concurrent development of hypertension, proteinuria, and oxidative stress in the placenta. In this study, we induced hypoxic stress in rats during pregnancy to reproduce physiological conditions associated with preeclampsia. The maternal weight of hypoxic pregnant rats was lower than that of normoxic animals. The level of calcium ions were also increased in urine collected from the hypoxic animals. In contrast, urinary concentrations of sodium, chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…In another study, NCKX3 was demonstrated to be expressed in the rat duodenum (27). NCKX3 in the basolateral membrane of intestinal tissue transports calcium to the blood, thus it has a key role in calcium absorption (41). Due to this function of NCKX3, abnormal expression of NCKX3 can induce decreased calcium absorption in the duodenum and calcium reabsorption in the kidney; furthermore, it may result in hypocalcemia and osteoporosis (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, NCKX3 was demonstrated to be expressed in the rat duodenum (27). NCKX3 in the basolateral membrane of intestinal tissue transports calcium to the blood, thus it has a key role in calcium absorption (41). Due to this function of NCKX3, abnormal expression of NCKX3 can induce decreased calcium absorption in the duodenum and calcium reabsorption in the kidney; furthermore, it may result in hypocalcemia and osteoporosis (42).…”
Section: Discussionmentioning
confidence: 99%
“…These channels are located in a variety of organs and have the ability to function at metabolically appropriate times (39). A number of previous studies have reported on the expression and regulation of various cation channel proteins; however, there are no similar reports for such proteins in canine organs (2,31,(39)(40)(41). Thus, in the present study, the organ-specific expression and localization of calcium (NCKX3, TRPV2), copper (CTR1, ATP7A), iron (IREG1) and ferroxidase for iron transporting (HEPH) proteins and mRNAs were investigated in the canine duodenum (upper part of the duodenum), kidney (borderline of the cortex and medulla), spleen (borderline of the white and red pulp) and liver (quadrate lobe of the liver).…”
Section: Discussionmentioning
confidence: 99%
“…Urinalysis strips indicated that L-NAME mice exhibited obvious proteinuria (+ + ∼ + ++), and the control group showed absent to mild proteinuria. Previous studies have reported that elevated abundance of HIF1α is related to preeclamptic symptoms, and its level is increased not only in the placentas but also in circulation (3,27). Figure 2 demonstrates HIF1α abundance was indeed increased in the aortic tissues of PE mice (p < 0.01).…”
Section: Downregulation Of Crl3 Function and The Accumulation Of Wnk Kinases Pde5 And Rhoa In Placentas And Spiral Arteries Of Pe Patientmentioning
confidence: 74%
“…This finding suggested a specific inhibitory effect of hypoxia on ecac expression. In rats, expression of the transient receptor potential vanilloid (TRPV) 5 and TRPV6 (orthologues of ECaC) was also found to decrease in the duodenum of animals exposed to hypoxia (Yang et al, 2013). In the present study, we also evaluated the effects of hypoxia on two hypocalcaemic hormones, stanniocalcin-1 (stc-1) and calcitonin (ct).…”
Section: Impact Of Hypoxia Exposure On Ionic Regulationmentioning
confidence: 92%